Why the Current Tax Rate Tells You Little: Competing For Mobile and Immobile Firms - Dominika Irma Langenmayr; Simmler Martin (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper analyses if, and to which extent, firms anticipate future tax rate changes. The weight of future tax rates in firms' location decisions may explain differences in the sensitivity of firms' location decision to current tax rates. Firms with high relocation costs, for example, are more sensitive to expected future changes in the tax rate, as they find it more costly to react to tax rate increases later. Governments react to this behavior by increasing the corporate tax rate if the share of firms with high relocation costs is high. We first derive these effects in a simple model and then test for them empirically, using the evolution of a new and highly immobile industry (wind turbines) for identification.
Keywords: H25; H71; F21; 330